Pengaruh Cerita Moral Terhadap Perilaku Prososial Anak - K.Tanaya, Katarina (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract, Harsh city life fosters behaviors harm others. Moral-value can internalized through a moral story that will encourage children to behave in prosocial manner. Sixteen moral story of sharing, cooperation, helpfulness, and act honestly given to the experimental group children twice a week. At week eight measured prosocial behavior. The measurement results were analyzed by t-test showed t = 18,149 (p < 0,01). The analysis showed the mean of prosocial behavior on experimental group (mean = 162,12) was significantly greater than control group (mean = 96,18). Key words: Moral story, prosocial behavior